High resolution MR eye protocol optimization: Comparison between 3D-CISS, 3D-PSIF and 3D-VIBE sequences. Issue 7 (November 2015) - Tsiapa, Irene; Tsilimbaris, Miltiadis K.; Papadaki, Efrosini; Bouziotis, Penelope; Pallikaris, Ioannis G.; Karantanas, Apostolos H.; Maris, Thomas G.
Abstract: Purpose: The purpose of this study was to compare selected MRI pulse sequences and to evaluate their utility for depicting specific anatomic regions in the eye. Methods: A High-Resolution (HR) 0.08 × 0.08 × 0.60 mm 3 MRI protocol was developed on a 1.5-T clinical system and applied in the left eye of an albino rabbit, utilizing a small field of view surface coil. The comprehensive MRI protocol consisted of two 3D (T2/T1)w sequences (3D-PSIF and 3D-CISS), and one 3D T1w sequence (3D-VIBE). The T1w 3D-VIBE sequence was acquired, before and after intravenous injection of 0.2 mmol/kgr gadolinium-DTPA. Signal-to-Noise Ratios (SNR) and Contrast-to-Noise Ratios (CNR) amongst specific eye anatomical areas were calculated for each sequence. The presence of artifacts was rated subjectively utilizing a 5 point scale. Results: 3D-PSIF and 3D-CISS provide better delineation and visualization of the eye as compared with 3D-VIBE sequences. 3D-CISS images present the highest SNR and revealed better discrimination of the ocular surrounding tissues; its basic drawback though is related to ghost artifacts appearing in the anterior chamber and resulting in the lowest image quality. In post-contrast imaging, the T1w 3D-VIBE sequence provided the best overall image quality. Moreover, 3D (T2/T1)w sequences can provide good anatomic depiction of the eye segments. Agreement between the two independent readers was good. Conclusions: Optimization of a comprehensive MR eye imaging protocol is achieved. A higher SNR, a better spatial resolution and a reduction of the total scan time were obtained, thus making clinical MRI systems more reliable in eye imaging. Highlights: High-resolution Magnetic Resonance Imaging (HR-MRI) of the eye. Optimization of MRI protocol at 1.5T clinical system for ocular imaging. High spatial resolution 0.08 × 0.08 × 0.60 mm 3 within a rapid scanning time (3.5 min). 3D (T2/T1)w sequences (3D-PSIF and 3D-CISS). 3D T1w sequence (3D-VIBE) pre and post-Gd injection.